Scleromyxedema concurrent with dermatomyositis and paraproteinemia: A case report - M. N. Starovoitova; O. V. Desinova; N. G. Guseva (Современная ревматология)
The paper describes the case of a female patient who had at least three diseases: scleromyxedema, dermatomyositis/polymyositis (DM/PM), and paraproteinemia (monoclonal gammopathy). The concurrence of these diseases determines the atypism of their clinical and morphological patterns, as well as refractoriness to performed therapy. Scleromyxedema preceded DM followed by paraproteinemia, which does not rule out its presence in an earlier period when the patent was not carefully examined. The specific feature of this case is scleromyxedema concurrent with DM that was prevalent in the clinical picture of the disease, by determining the severity of the patient’s status and the need to be treated with high-dose glucocorticoids in combination with immunosuppressive drugs. There was no evidence for scleroderma systematica that was supposed to be present in the patient who had scleroderma-like skin involvement.The authors have repeatedly mentioned the concurrency pattern of scleroderma diseases, which reflects the close mechanisms of their development and hinders the identification of specific nosological entities. In this observation, the concurrence of scleromyxedema and DM complements a group of overlap diseases observed in dermatology and rheumatology.Paraproteinemia characteristic of scleromyxedema is occasionally encountered in systemic connective tissue diseases. The patient had monoclonal gammopathy that is most common in scleromyxedema. No signs of myeloma and tumors were seen. Classical paraneoplastic DM/PM was not detected either, which does not rule out the fact that the mechanism responsible for the development of this syndrome and the disease is similar in the patient described.